“TABIATSHUNOSLIK VA UNI O‘QITISH METODIKASI” FANI “QUYOSH SISTEMASI, SAYYORALAR” MAVZUSINI INTERFAOL METODLAR VOSITASIDA O‘RGANISH ORQALI TALABALARNI MA’NAVIY FAOLIYATGA METODIK TAYYORLASH - Shodiyev, N.; Nabiyeva, D.; Shadiyev, R. (SCIENCE and SOCIETY, 2024)
In this article, in the process of education, the scientific heritage of scholars and thinkers of Movaraunnahr and the achievements of our science in this field will be absorbed into the educational content. dedicated.
Keywords: educational process; heritage of great scholars and thinkers; methodology; interactive educational methods; Solar system; Exo Solar system; academy; observatory; “Zij”; “Samarkand” planet